Piezoelectric ceramic substrate and preparation method thereof
By adding barium titanate microcrystalline glass to piezoelectric ceramics in potassium sodium niobate-bismuth zirconate, the problems of lower piezoelectric coefficient and high electrode cost caused by high temperature sintering are solved, and lower sintering temperature and higher piezoelectric properties.
Patent Information
- Application Number
- CN202411280021.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
Existing lead-free piezoelectric ceramic materials are prone to hole defects during high-temperature sintering, resulting in a decrease in the piezoelectric coefficient, and the use of expensive electrodes such as silver palladium and silver platinum, which increases the cost.
Add barium titanate microcrystalline glass to potassium sodium niobate-bismuth zirconate piezoelectric ceramics to adjust the sintering temperature, reduce the volatility of Na+, K+ and Bi2+, reduce the sintering temperature, and reduce the dependence on the electrode.
The sintering temperature is reduced from 1150℃ to about 900℃, which increases the piezoelectric coefficient, reduces the need to use expensive electrodes, and reduces product costs.
Smart Images

Figure CN119118664A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a piezoelectric ceramic substrate and a preparation method thereof, belonging to the technical field of functional ceramic materials. Background Art
[0002] Piezoelectric ceramics can realize the conversion between mechanical and electrical energy, and are widely used in ultrasonic transducers, non-destructive testing, communication technology, energy, sensors, aerospace technology and other fields. Currently, piezoelectric ceramics on the market contain a large amount of lead, and the most common is lead zirconate titanate (PZT)-based piezoelectric ceramic materials. Lead oxide will cause serious harm to the environment during production and use, and the same problem exists in the disposal of its waste after disposal, which will cause damage to the ecosystem on which human beings depend for survival. Therefore, lead-free piezoelectric ceramics are the trend of future development.
[0003] 0.96K 0.48 Na 0.52 Nb 0.98 Sb 0.02 O3-0.04Bi 0.5 Na 0.5 ZrO3 (potassium sodium niobate-sodium bismuth zirconate, KNN-BNZ) is a lead-free piezoelectric ceramic with excellent performance, but the sintering temperature is relatively high, about 1150°C; and the high temperature sintering process Na + , K + and Bi 2+ The volatilization of ions can easily lead to defects such as cavities inside the ceramic, resulting in a decrease in the piezoelectric coefficient (D33) of the piezoelectric ceramic, thereby reducing the performance of the piezoelectric ceramic. In addition, due to the high sintering temperature, expensive electrodes such as silver palladium and silver platinum must be used, which makes it difficult to reduce the cost of piezoelectric ceramics. Summary of the invention
[0004] In view of this, the present invention proposes an improved piezoelectric ceramic substrate and a preparation method thereof, by adding barium titanate glass-ceramics to reduce the sintering temperature of KNN-BNZ piezoelectric ceramics, so as to solve the problem that the piezoelectric coefficient of existing KNN-BNZ piezoelectric ceramics decreases at higher sintering temperatures and expensive electrodes such as silver palladium and silver platinum must be used.
[0005] According to one aspect of the present invention, a piezoelectric ceramic substrate is proposed, comprising a potassium sodium niobate-sodium bismuth zirconate piezoelectric ceramic material component and a barium titanate glass-ceramic material component; in the piezoelectric ceramic substrate, the molar ratio of the element Nb in the potassium sodium niobate-sodium bismuth zirconate piezoelectric ceramic material component to the element Ba in the barium titanate glass-ceramic material component is Nb:Ba=(97~99.9):(0.01~3).
[0006] Furthermore, the sodium potassium niobate-sodium bismuth zirconate piezoelectric ceramic material components contain K, Na, Nb, Sb, Bi, and Zr elements, and the molar ratio is K:Na:Nb:Sb:Bi:Zr=(22.04~24.04):(24.96~26.96):(46.04~48.04):(0.46~1.46):(0.5~1.5):(1.5~2.5).
[0007] Furthermore, the raw material components of the sodium potassium niobate-sodium bismuth zirconate piezoelectric ceramic material component include:
[0008] K2O: 21.59~23.59mol%
[0009] Na2O: 24.45~26.45mol%
[0010] Nb2O5: 45.12~47.12mol%
[0011] Sb2O3: 0.44~1.44mol%
[0012] Bi2O3: 0.48~1.48mol%
[0013] ZrO2: 2.92~4.92mol%.
[0014] Furthermore, the barium titanate glass-ceramic material components contain Ba, Ti, Al, and Si elements, and the molar ratio is Ba:Ti:Al:Si=(30-45):(30-45):(10-20):(10-30).
[0015] Furthermore, the raw material components of the barium titanate glass-ceramic material component include:
[0016] BaO: 30-45 mol%
[0017] TiO2: 30~45mol%
[0018] Al2O3: 5~10mol%
[0019] SiO2: 10~30mol%.
[0020] According to another aspect of the present invention, a method for preparing a piezoelectric ceramic substrate is also proposed, which is used to prepare the aforementioned piezoelectric ceramic substrate, and the preparation method comprises: weighing prepared potassium sodium niobate-sodium bismuth zirconate piezoelectric ceramic powder and barium titanate glass-ceramics powder in proportion, wherein the potassium sodium niobate-sodium bismuth zirconate piezoelectric ceramic powder accounts for 95.0-99.5wt%, and the barium titanate glass-ceramics powder accounts for 0.5-5wt%; subjecting the weighed mixed powder of the potassium sodium niobate-sodium bismuth zirconate piezoelectric ceramic powder and the barium titanate glass-ceramics powder to rolling ball milling, granulation, pressing, debinding, and sintering in sequence to obtain the piezoelectric ceramic substrate; the molar ratio of element Nb to element Ba in the piezoelectric ceramic substrate is Nb:Ba=(97-99.9):(0.01-3).
[0021] Furthermore, the sodium potassium niobate-sodium bismuth zirconate piezoelectric ceramic powder contains K, Na, Nb, Sb, Bi, and Zr elements, and the molar ratio is K:Na:Nb:Sb:Bi:Zr=(22.04-24.04):(24.96-26.96):(46.04-48.04):(0.46-1.46):(0.5-1.5):(1.5-2.5).
[0022] Furthermore, the method further comprises: taking a piezoelectric ceramic raw material to prepare the sodium potassium niobate-sodium bismuth zirconate piezoelectric ceramic powder; wherein the piezoelectric ceramic raw material comprises the following components:
[0023] K2O: 21.59~23.59mol%
[0024] Na2O: 24.45~26.45mol%
[0025] Nb2O5: 45.12~47.12mol%
[0026] Sb2O3: 0.44~1.44mol%
[0027] Bi2O3: 0.48~1.48mol%
[0028] ZrO2: 2.92~4.92mol%.
[0029] Furthermore, the barium titanate glass-ceramic powder contains Ba, Ti, Al, and Si elements, and the molar ratio is Ba:Ti:Al:Si=(30-45):(30-45):(10-20):(10-30).
[0030] Furthermore, the method further comprises: preparing the barium titanate glass-ceramic powder from a glass-ceramic raw material; wherein the glass-ceramic raw material comprises the following components:
[0031] BaO: 30-45 mol%
[0032] TiO2: 30~45mol%
[0033] Al2O3: 5~10mol%
[0034] SiO2: 10-30 mol%;
[0035] The particle size of the barium titanate glass-ceramic powder is between 0.1 microns and 5 microns.
[0036] Compared with the prior art, the beneficial effects of the technical solution of the present invention are as follows: by adding barium titanate microcrystalline glass to the potassium sodium niobate-sodium bismuth zirconate (KNN-BNZ) piezoelectric ceramic component to assist sintering, the sintering temperature of the original KNN-BNZ piezoelectric ceramic can be reduced from 1150°C to about 900°C, which reduces the Na + , K + and Bi 2+ The volatilization of silver can reduce the internal defects caused by high-temperature sintering, thereby improving the piezoelectric coefficient. On the other hand, the lower sintering temperature does not need to use expensive silver-palladium, silver-platinum and other electrodes, thus reducing product costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The figure is a flow chart of preparing a piezoelectric ceramic substrate according to an embodiment of the present invention.
[0038] Figure 2 This is a cross-sectional microstructure diagram of a piezoelectric ceramic substrate when the weight percentage of barium titanate glass-ceramics added is 4wt%.
[0039] Figure 3 This is the cross-sectional microstructure diagram of the piezoelectric ceramic substrate when the weight percentage of barium titanate microcrystalline glass added is 1wt%.
[0040] Figure 4 This is a cross-sectional microstructure diagram of a piezoelectric ceramic substrate when the weight percentage of barium titanate glass-ceramics added is 2wt%. DETAILED DESCRIPTION
[0041] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods and examples. It should be understood that the purpose of providing the examples is only to illustrate, rather than to limit the scope of protection of the present invention.
[0042] A specific embodiment of the present invention provides a piezoelectric ceramic substrate, which comprises a potassium sodium niobate-sodium bismuth zirconate (KNN-BNZ) piezoelectric ceramic material component and a barium titanate glass-ceramic material component; wherein the KNN-BNZ piezoelectric ceramic material component contains K, Na, Nb, Sb, Bi, and Zr elements, and the molar ratio is K:Na:Nb:Sb:Bi:Zr=(22.04-24.04):(24.96-26.96):(46.04-4 8.04):(0.46~1.46):(0.5~1.5):(1.5~2.5); the barium titanate glass-ceramic material contains Ba, Ti, Al, and Si elements, and the molar ratio is Ba:Ti:Al:Si=(30~45):(30~45):(10~20):(10~30); and in the piezoelectric ceramic substrate, the molar ratio of element Nb to element Ba is Nb:Ba=(97~99.9):(0.01~3). Adding barium titanate glass-ceramic can significantly reduce the sintering temperature of KNN-BNZ piezoelectric ceramics. The lower sintering temperature can alleviate the Na in the ceramics. + , K + and Bi 2+ The volatilization of Pd increases the piezoelectric constant (D33) of the ceramic, and reduces the Pd content in the electrode, thereby reducing costs.
[0043] In some preferred embodiments, the raw material components of the KNN-BNZ piezoelectric ceramic material component in the piezoelectric ceramic substrate of the present invention include:
[0044] K2O: 21.59~23.59mol%
[0045] Na2O: 24.45~26.45mol%
[0046] Nb2O5: 45.12~47.12mol%
[0047] Sb2O3: 0.44~1.44mol%
[0048] Bi2O3: 0.48~1.48mol%
[0049] ZrO2: 2.92~4.92mol%;
[0050] The raw material components of the barium titanate glass-ceramic material components include:
[0051] BaO: 30-45 mol%
[0052] TiO2: 30~45mol%
[0053] Al2O3: 5~10mol%
[0054] SiO2: 10~30mol%.
[0055] The specific embodiment of the present invention also proposes a method for preparing the above-mentioned piezoelectric ceramic substrate, referring to Figure 1 , the preparation method comprises:
[0056] 1) preparing KNN-BNZ piezoelectric ceramic powder by taking piezoelectric ceramic raw materials;
[0057] 2) preparing barium titanate glass-ceramic powder by taking glass-ceramic raw materials;
[0058] 3) The prepared KNN-BNZ piezoelectric ceramic powder and barium titanate glass-ceramic powder are weighed in proportion, and the aforementioned piezoelectric ceramic substrate is obtained after rolling ball milling, granulation, pressing, debinding, and sintering.
[0059] In the above step 1), the piezoelectric ceramic raw material used comprises the following components:
[0060] K2O: 21.59~23.59mol%
[0061] Na2O: 24.45~26.45mol%
[0062] Nb2O5: 45.12~47.12mol%
[0063] Sb2O3: 0.44~1.44mol%
[0064] Bi2O3: 0.48~1.48mol%
[0065] ZrO2: 2.92~4.92mol%.
[0066] In the above step 2), the glass-ceramic raw material used comprises the following components:
[0067] BaO: 30-45 mol%
[0068] TiO2: 30~45mol%
[0069] Al2O3: 5~10mol%
[0070] SiO2: 10~30mol%.
[0071] In some specific embodiments, the aforementioned step 1) prepares KNN-BNZ piezoelectric ceramic powder, specifically comprising:
[0072] 100-500 g of piezoelectric ceramic raw material is weighed and placed in a polytetrafluoroethylene plastic bottle, 50-250 g of ethanol is poured into the raw material, and the raw material is rolled and ball-milled at a speed of 500-1200 rpm for 6-24 h; after ball-milling, the raw material is dried at a temperature of 60-100° C. for 12-24 h to remove the ethanol; the raw material powder after drying is heated to 750-900° C. at a speed of 1-10° C. / min and pre-fired for 2-10 h; 50-100 g of the pre-fired powder is placed in an agate pot, 50-100 g of ethanol and 150-300 g of 3-10 mm zirconium balls are added, the raw material is ball-milled at a speed of 500-1000 rpm for 6-24 h, and then the raw material is dried at a temperature of 60-100° C. for 12-24 h to remove the ethanol, so as to obtain KNN-BNZ piezoelectric ceramic powder.
[0073] The aforementioned step 2) of preparing barium titanate glass-ceramics powder specifically comprises:
[0074] Weigh 100-500g of microcrystalline glass raw material and put it in a polytetrafluoroethylene plastic bottle, and roll ball mill at a speed of 500-1200rpm for 6-12h; after ball milling, smelt at a temperature of 1300-1500℃ for 0.5-4h, and then pour into deionized water for quenching to obtain glass slag; take 50-100g of glass slag and put it in an agate pot, add 50-100g of ethanol and 150-300g of 3-10mm zirconium balls, and then ball mill at a speed of 800-1000rpm for 4-24h, and then put it at a temperature of 60-100℃ and dry it for 12-24h to remove ethanol, so as to obtain barium titanate microcrystalline glass powder with a particle size between 0.1 micron and 5 microns.
[0075] The aforementioned step 3) uses KNN-BNZ piezoelectric ceramic powder and barium titanate glass-ceramic powder to prepare a piezoelectric ceramic substrate, specifically comprising:
[0076] Weigh 100-200 g of KNN-BNZ piezoelectric ceramic powder and barium titanate glass-ceramic powder in proportion (of which KNN-BNZ piezoelectric ceramic powder accounts for 95.0-99.5 wt %, and barium titanate glass-ceramic powder accounts for 0.5-5 wt %), put them in a polytetrafluoroethylene plastic bottle, pour 50-100 g of ethanol into it, and roll-mill at a speed of 500-1000 rpm for 6-24 h; after ball milling, dry it at a temperature of 60-100 ° C for 12-24 h to remove ethanol. Alcohol, take 50-100g of the dried raw material, add 2-10g of PVB alcohol solution with a concentration of 5-10wt% to granulate, and pass through an 80-mesh sieve; weigh 0.5-1g of the sieved raw material, press it into shape at 100-200MPa, put it in a sintering furnace and heat it to 450-600℃ at 1-2℃ / min to remove binder for 2-4h; then continue to heat it to 900-1000℃ at 3-10℃ / min and keep it warm for 1-3h to obtain the aforementioned piezoelectric ceramic substrate.
[0077] Inspection of KNN-BNZ ceramics in the prepared piezoelectric ceramic substrate: The prepared piezoelectric ceramic substrate can be used to detect the microscopic morphology and structure of the ceramic by SEM and XRD, and the type and content of some elements in the ceramic can be analyzed by TEM and electron probe X-ray microanalyzer.
[0078] Inspection of barium titanate glass-ceramics in the prepared piezoelectric ceramic substrate: The prepared piezoelectric ceramic substrate can be used to detect the components of the glass-ceramics crystallization by SEM and XRD, and the element types and contents of the glass-ceramics part can be analyzed by TEM and electron probe X-ray microanalyzer.
[0079] Example 1
[0080] 1) Weigh piezoelectric ceramic raw materials: K2O (22.59 mol%), Na2O (25.45 mol%), Nb2O5 (46.12 mol%), Sb2O3 (0.94 mol%), Bi2O3 (0.98 mol%) and ZrO2 (3.92 mol%), a total of 200 g, put it in a polytetrafluoroethylene plastic bottle, pour 100 g of ethanol and roll ball mill at 800 rpm for 12 h; the ball-milled raw materials are dried at 80°C for 18 h to remove ethanol; the dried raw material powder is heated to 850°C at 5°C / min and pre-fired for 2 h; take 100 g of the pre-fired powder and put it in an agate jar, add 50 g of ethanol and 300 g of 5 mm zirconium balls, ball mill at 800 rpm for 12 h, and then dry at 70°C for 18 h to remove ethanol to prepare KNN-BNZ piezoelectric ceramic powder.
[0081] 2) Weighing glass-ceramic raw materials: BaO (33 mol%), TiO2 (33 mol%), Al2O3 (5 mol%) and SiO2 (29 mol%), a total of 200 g, put them in a polytetrafluoroethylene plastic bottle, and roll ball mill at 800 rpm for 12 h; the ball-milled raw materials are smelted at 1400°C for 1 h and poured into deionized water for quenching to prepare glass slag; 100 g of the glass slag is put in an agate jar, 100 g of ethanol and 300 g of 5 mm zirconium balls are added, and the mixture is ball milled at 800 rpm for 12 h, and then dried at 800°C for 18 h to remove ethanol to prepare barium titanate glass-ceramic powder.
[0082] 3) Weigh a total of 100 g of the KNN-BNZ piezoelectric ceramic powder and barium titanate glass-ceramic powder prepared above (of which KNN-BNZ piezoelectric ceramic powder accounts for 96.0 wt% and barium titanate glass-ceramic powder accounts for 4 wt%), put them in a polytetrafluoroethylene plastic bottle, pour 50 g of ethanol into it, and then roll ball mill at a speed of 800 rpm for 18 hours; the ball-milled raw material is dried at a temperature of 70°C for 18 hours to remove the ethanol; take 50 g of the dried raw material, add 6 g of PVB alcohol solution with a concentration of 5 wt% for granulation and pass through an 80-mesh sieve; weigh 0.5 g of the sieved raw material, press it into shape at 120 MPa, put it in a sintering furnace and heat it to 550°C at 2°C / min to remove the binder for 4 hours; then continue to heat it to 900°C at 5°C / min and keep it warm for 2 hours to obtain a piezoelectric ceramic substrate.
[0083] In this embodiment, in step 3), 4 wt% (weight percentage of the total weight of the two powders) of barium titanate glass-ceramic powder is added when preparing the piezoelectric ceramic substrate, so that the sintering temperature of the ceramic substrate is reduced from 1150°C to 900°C.
[0084] The sintering temperature of the prepared piezoelectric ceramic substrate is 900℃, the piezoelectric constant D33 of the tested ceramic is 350pC / N, and the cross-sectional SEM test data is as follows: Figure 2 As shown, glass-ceramics are clearly distinguished from ceramics, and the ceramic substrate can be analyzed for element types and contents using a more precise X-ray microanalyzer.
[0085] Example 2
[0086] The difference between this embodiment and embodiment 1 is that in step 3), when the piezoelectric ceramic substrate is prepared using KNN-BNZ piezoelectric ceramic powder and barium titanate glass-ceramic powder, the weight proportions of the two powders are different. In this embodiment, the total weight of KNN-BNZ piezoelectric ceramic powder and barium titanate glass-ceramic powder is 100g, of which KNN-BNZ piezoelectric ceramic powder accounts for 99.0wt% and barium titanate glass-ceramic powder accounts for 1wt%. Under such a ratio, the sintering process after debinding is kept at 975°C for 2h, and the piezoelectric constant D33 of the obtained piezoelectric ceramic substrate test ceramic is 450pC / N.
[0087] In this example, 1 wt% of barium titanate glass-ceramic powder is added when preparing the piezoelectric ceramic substrate in step 3), so that the sintering temperature of the piezoelectric ceramic substrate is reduced from 1150°C to 975°C. The SEM test data of the cross section of the piezoelectric ceramic substrate is shown in Figure 2. Figure 3 As shown, there is a clear distinction between glass and ceramics. The glass content is lower, the substrate has a good degree of densification, fewer pores and a small volume, and the element types and contents can be analyzed using a more precise X-ray microanalyzer.
[0088] Example 3
[0089] In this embodiment, the steps for preparing KNN-BNZ piezoelectric ceramic powder (including parameters, dosage, process conditions, etc.) are the same as those in Example 1;
[0090] In step 2), when preparing barium titanate glass-ceramics powder, 200 g of BaO (41 mol%), TiO2 (41 mol%), Al2O3 (8 mol%) and SiO2 (10 mol%) were weighed, and the rest was the same as that of Example 1, to obtain barium titanate glass-ceramics powder;
[0091] In this embodiment, a total of 100g of the prepared KNN-BNZ piezoelectric ceramic powder and barium titanate glass-ceramic powder are taken, wherein the KNN-BNZ piezoelectric ceramic powder accounts for 96.0wt% and the barium titanate glass-ceramic powder accounts for 4wt%. In this embodiment, a different ratio of the raw material components of barium titanate glass-ceramic is used, and the sintering process after debinding is kept at 910°C for 2h. Compared with the case without adding barium titanate glass-ceramic, the sintering temperature of the piezoelectric ceramic is reduced from 1150°C to 910°C, and the piezoelectric constant D33 of the obtained piezoelectric ceramic substrate test ceramic is 370pC / N.
[0092] Example 4
[0093] In this embodiment, the process parameters, materials, etc. of step 1) for preparing KNN-BNZ piezoelectric ceramic powder and step 2) for preparing barium titanate glass-ceramic powder are the same as those of embodiment 3.
[0094] The difference between this embodiment and embodiment 3 is that in step 3), when the piezoelectric ceramic substrate is prepared using KNN-BNZ piezoelectric ceramic powder and barium titanate glass-ceramic powder, the weight proportions of the two powders are different. In this embodiment, the total weight of KNN-BNZ piezoelectric ceramic powder and barium titanate glass-ceramic powder is 100g, of which KNN-BNZ piezoelectric ceramic powder accounts for 98.0wt% and barium titanate glass-ceramic powder accounts for 2wt%. Under such a ratio, the sintering process after debinding is kept at 950°C for 2h.
[0095] Compared with the prior art that does not add barium titanate glass-ceramics, 2wt% of barium titanate glass-ceramics powder is added when preparing the piezoelectric ceramic substrate in this example, so that the sintering temperature of the piezoelectric ceramic is reduced from 1150℃ to 950℃. The piezoelectric constant D33 of the prepared piezoelectric ceramic substrate is 430pC / N. The SEM test data of the cross section of the piezoelectric ceramic substrate is as follows: Figure 4 As shown, there is a clear distinction between glass and ceramics. The glass content is higher, the substrate is well densified and the pores are smaller. The type and content of elements can be analyzed using a more precise X-ray microanalyzer.
[0096] Example 5
[0097] In this embodiment, the process parameters, materials, etc. of step 1) for preparing KNN-BNZ piezoelectric ceramic powder and step 2) for preparing barium titanate glass-ceramic powder are the same as those of embodiment 3.
[0098] The difference between this embodiment and embodiment 3 is that, in step 3), when the piezoelectric ceramic substrate is prepared using KNN-BNZ piezoelectric ceramic powder and barium titanate glass-ceramic powder, the weight proportions of the two powders are different. In this embodiment, the total weight of KNN-BNZ piezoelectric ceramic powder and barium titanate glass-ceramic powder is 100g, of which KNN-BNZ piezoelectric ceramic powder accounts for 99.0wt% and barium titanate glass-ceramic powder accounts for 1wt%. Under such a ratio, the sintering process after debinding is kept at 900°C for 2h.
[0099] In this example, 1 wt% of barium titanate glass-ceramic powder was added when preparing the piezoelectric ceramic substrate, so that the sintering temperature of the piezoelectric ceramic substrate was reduced from 1150° C. to 900° C. The piezoelectric constant D33 of the prepared piezoelectric ceramic substrate was 478 pC / N.
[0100] Comparative Example 1
[0101] In this comparative example, no barium titanate glass-ceramic powder is added, and the KNN-BNZ piezoelectric ceramic substrate is prepared directly using the KNN-BNZ piezoelectric ceramic powder prepared in Example 1, which specifically includes:
[0102] Take 50g of the KNN-BNZ piezoelectric ceramic powder prepared in Example 1, add 6g of 5wt% PVB alcohol solution to granulate and pass through an 80-mesh sieve, weigh 0.5g of the sieved raw material, press it under 120MPa, put it in a sintering furnace and heat it to 550℃ for 4h to remove the binder, continue to heat it to 1150℃ for 2h at 5℃ / min, and prepare a KNN-BNZ piezoelectric ceramic substrate. The piezoelectric constant D33 of the KNN-BNZ piezoelectric ceramic substrate is 430pC / N.
[0103] Comparative Example 2
[0104] The comparative example does not add barium titanate microcrystalline glass powder, and directly uses the KNN-BNZ piezoelectric ceramic powder prepared in Example 1 to prepare the KNN-BNZ piezoelectric ceramic substrate, specifically comprising: taking 50g of the KNN-BNZ piezoelectric ceramic powder prepared in Example 1, adding 6g of PVB alcohol solution with a concentration of 5wt%, granulating and passing through an 80-mesh sieve, weighing 0.5g of the sieved raw material, pressing and molding at 120MPa, placing it in a sintering furnace and heating it to 550℃ at 2℃ / min for 4h to remove the binder; continuing to heat it to 1155℃ at 5℃ / min and keep it warm for 2h to prepare the KNN-BNZ piezoelectric ceramic substrate. The KNN-BNZ piezoelectric ceramic substrate is taken to test the ceramic piezoelectric constant D33 of 390pC / N.
[0105] It can be seen that when preparing KNN-BNZ piezoelectric ceramics, the addition of barium titanate glass-ceramics can greatly reduce the ceramic sintering temperature (from 1150°C to about 900°C), which can reduce the cost of ceramic substrate metallization; further, when the addition amount of barium titanate glass-ceramics is within a certain range (such as about 1wt%), the sintering temperature can be greatly reduced, and the piezoelectric constant D33 of the obtained piezoelectric ceramic substrate can be increased to 478pC / N.
[0106] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art of the present invention, several equivalent substitutions or obvious variations can be made without departing from the concept of the present invention, and the performance or use is the same, which should be regarded as belonging to the protection scope of the present invention.
Claims
1. A piezoelectric ceramic substrate, characterized in that: It contains sodium potassium niobate-sodium bismuth zirconate piezoelectric ceramic material components and barium titanate microcrystalline glass material components; In the piezoelectric ceramic substrate, the molar ratio of the element Nb in the sodium potassium niobate-sodium bismuth zirconate piezoelectric ceramic material component to the element Ba in the barium titanate glass-ceramic material component is Nb:Ba=(97-99.9):(0.01-3).
2. The piezoelectric ceramic substrate according to claim 1, characterized in that: The sodium potassium niobate-sodium bismuth zirconate piezoelectric ceramic material components contain K, Na, Nb, Sb, Bi, and Zr elements, and the molar ratio is K:Na:Nb:Sb:Bi:Zr=(22.04-24.04):(24.96-26.96):(46.04-48.04):(0.46-1.46):(0.5-1.5):(1.5-2.5).
3. The piezoelectric ceramic substrate according to claim 2, characterized in that: The raw material components of the sodium potassium niobate-sodium bismuth zirconate piezoelectric ceramic material component include: K2O: 21.59~23.59mol% Na2O: 24.45~26.45mol% Nb2O5: 45.12~47.12mol% Sb2O3: 0.44~1.44mol% Bi2O3: 0.48~1.48mol% ZrO2: 2.92~4.92mol%.
4. The piezoelectric ceramic substrate according to claim 1, characterized in that: The barium titanate glass-ceramic material components contain Ba, Ti, Al, and Si elements, and the molar ratio is Ba:Ti:Al:Si=(30-45):(30-45):(10-20):(10-30).
5. The piezoelectric ceramic substrate according to claim 4, characterized in that: The raw material components of the barium titanate glass-ceramic material component include: BaO: 30-45 mol% TiO2: 30~45mol% Al2O3: 5~10mol% SiO2: 10~30mol%.
6. A method for preparing a piezoelectric ceramic substrate, characterized in that: include: Weigh the prepared sodium potassium niobate-sodium bismuth zirconate piezoelectric ceramic powder and barium titanate glass-ceramics powder in proportion, wherein the sodium potassium niobate-sodium bismuth zirconate piezoelectric ceramic powder accounts for 95.0-99.5wt% and the barium titanate glass-ceramics powder accounts for 0.5-5wt%; The mixed powder of the weighed potassium sodium niobate-sodium bismuth zirconate piezoelectric ceramic powder and the barium titanate microcrystalline glass powder is subjected to rolling ball milling, granulation, pressing molding, debinding and sintering in sequence to obtain the piezoelectric ceramic substrate; the molar ratio of the element Nb to the element Ba in the piezoelectric ceramic substrate is Nb:Ba=(97-99.9):(0.01-3).
7. The preparation method according to claim 6, characterized in that: The sodium potassium niobate-sodium bismuth zirconate piezoelectric ceramic powder contains K, Na, Nb, Sb, Bi, and Zr elements, and the molar ratio is K:Na:Nb:Sb:Bi:Zr=(22.04-24.04):(24.96-26.96):(46.04-48.04):(0.46-1.46):(0.5-1.5):(1.5-2.5).
8. The preparation method according to claim 7, characterized in that: The invention also includes: taking a piezoelectric ceramic raw material to prepare the sodium potassium niobate-sodium bismuth zirconate piezoelectric ceramic powder; wherein the piezoelectric ceramic raw material comprises the following components: K2O: 21.59~23.59mol% Na2O: 24.45~26.45mol% Nb2O5: 45.12~47.12mol% Sb2O3: 0.44~1.44mol% Bi2O3: 0.48~1.48mol% ZrO2: 2.92~4.92mol%.
9. The preparation method according to claim 6, characterized in that: The barium titanate glass-ceramic powder contains Ba, Ti, Al, and Si elements, and the molar ratio is Ba:Ti:Al:Si=(30-45):(30-45):(10-20):(10-30).
10. The preparation method according to claim 9, characterized in that: Also includes: The barium titanate glass-ceramic powder is prepared from a glass-ceramic raw material; wherein the glass-ceramic raw material comprises the following components: BaO: 30-45 mol% TiO2: 30~45mol% Al2O3: 5~10mol% SiO2: 10-30 mol%; The particle size of the barium titanate glass-ceramic powder is between 0.1 micrometers and 5 micrometers.
Citation Information
Patent Citations
KNN-based (sodium potassium niobate-based) energy storage microcrystalline glass material with ultralow dielectric loss and preparation method
CN106865989A
Piezoelectric ceramic and method of producing the same
JP2005179144A
Piezoelectric ceramic and piezoelectric element
WO2024095963A1
